A Review on Development of Social Entrepreneurship Projects among Indigenous People - Binti Ahmad , Aminah; Sarah Maidin, Siti (International Journal of Psychosocial Rehabilitation, 2019)
This paper aims to present a systematic literature review which illustrates the development of social entrepreneurship projects among indigenous people. This literature also examines the various characteristics of indigenous entrepreneurship projects. The research is based on a review of 15 different sources from the literature. Different research databases containing peer - reviewed articles and general online resources were utilized to gather the information. The outcome from the review revealed that there is potential for the indigenous people to be engaged in social entrepreneurship.